Solicitors' Liability Against Client And Third Party - Mohd Fuad, Husaini (2013)
The reason for writing this article can be summarised in one short comment from a practising lawyer: 'Anecdotal evidence suggests that over the last few decades the average ... solicitor ... has increasingly faced clients who are very demanding, pay as little as they can, have little respect for their advisers, and do not hesitate to blame them if anything goes wrong. One may argue as to whether or not these changes are for the better, but it must be highly likely that they have led to an increase in litigation against (solicitors)' (Evan H 2005).3 This increase in litigation and case law has generated the need for high quality comprehensive accounts of the law in this area. This article will present a comprehensive and (as far as it is practical in a complex and technical area) accessible account of the law relating to solicitors' liability. This is to offer a clearly written structured work, with a depth of analysis sufficient to meet the needs of both practitioner and academic readers. The title of this article describes precisely the aims and objective of this article, which provides a statement of the accepted principles of good conduct and practice for solicitors, as against the clients and third party.